Functional performance among children with cochlear implants and additional disabilities. (1st September 2013) - Meinzen-Derr, Jareen; Wiley, Susan; Grether, Sandra; Choo, Daniel I.
Abstract : Objective To assess daily functional skills among young cochlear implant (CI) recipients with additional disabilities. Methods Children with CI and developmental disabilities and a hearing control group containing similar ages and similar disabilities were enrolled in a cross-sectional study of language and functional skills. Daily functional skills were measured using the Pediatric Evaluation of Disability Inventory (PEDI), which provides standard and scaled scores in Self-Care, Mobility, and Social Functioning domains. Language was assessed using the Preschool Language Scales, 4th edition which provides standard scores and age equivalents. Results Fourteen children with CIs and seven hearing controls were included in this analysis. Most children in this study (90.5%) had cognitive disabilities and 57% had motor disabilities. Compared with the hearing controls, children with CIs were less likely to have functional independence in any PEDI domain. Children with CI had significantly lower median social functioning standard scores compared with controls (17.3 vs. 27.5, P = 0.009). After controlling for nonverbal cognitive abilities and language level, the difference was no longer significant (19.1 vs. 24, P = 0.3). Among children with CI, age at implant and duration with device were not associated ( P > 0.4) with PEDI scores. Discussion Although children with CI and developmental disabilities had similar functional skills as hearing children with similar disabilities regarding the PEDI domains of Self-Care and Mobility, they had lower Social Function standard scores. This lower social functioning among children with implants may be related to lower language levels and possible language deficits seen in the CI group. Regular assessments of functional abilities coupled with language abilities are essential in providing every child with the opportunity for maximizing the potential for independence.